Gamifying soft skills in the University of Aveiro - Ribeiro, André Alvarez Girão (2021)
The need for future employees to show skill beyond that of “hard” knowledge is growing in several industries of the job market. To address the changing expectations of future employers and to guarantee a prosperous professional life, higher education institutions (HEI) are making increasing efforts to provide their students with soft skills, which go beyond that of the traditional courses’ curriculum. Therefore, HEIs are faced with the challenge of teaching transversal competencies to their students while ensuring that their development is authenticated and valued by employing organizations. To this end, open badging and micro-credentials are increasingly being employed, since they provide an answer for both the need for soft skill validation and for motivating their development. Digital badges have been subject to educational research in recent years, with results which point to a successful relationship between gamification, badges and learning outcomes. This work aims to further this research by establishing a theoretical framework for implementing a digital badge strategy to encourage students to perform activities that promote the development of soft skills. Our findings will inform the creation of a badge system suited be adapted and applied to various learning contexts and institutions.